2017
DOI: 10.1002/mma.4665
|View full text |Cite
|
Sign up to set email alerts
|

Lie symmetries of a system arising in plasma physics

Abstract: Lie group classification for a diffusion‐type system that has applications in plasma physics is derived. The classification depends on the values of 5 parameters that appear in the system. Similarity reductions are presented. Certain initial value problems are reduced to problems with the governing equations being ordinary differential equations. Examples of potential symmetries are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…An important benefit of the potential symmetry analysis is the disclosure of linearizing mappings. Lie symmetry analysis of the nonlinear system () did not provide such mappings 4 . However, in this work we have shown that some of its auxiliary systems admit infinite dimensional symmetries that lead to linearizing mappings.…”
Section: Remarks and Further Studymentioning
confidence: 84%
See 4 more Smart Citations
“…An important benefit of the potential symmetry analysis is the disclosure of linearizing mappings. Lie symmetry analysis of the nonlinear system () did not provide such mappings 4 . However, in this work we have shown that some of its auxiliary systems admit infinite dimensional symmetries that lead to linearizing mappings.…”
Section: Remarks and Further Studymentioning
confidence: 84%
“…Here we continue the work of Charalambous and Sophocleous, 4 where Lie symmetries of the system () were classified. Our goal is to derive nonlocal symmetries and other nonlocal transformations.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations